2022
DOI: 10.1097/shk.0000000000002008
|View full text |Cite
|
Sign up to set email alerts
|

Shock Induces Endothelial Permeability After Trauma Through Increased Activation of Rhoa Gtpase

Abstract: Introduction: Severely injured patients develop a dysregulated inflammatory state characterized by vascular endothelial permeability, which contributes to multiple organ failure. To date, however, the mediators of and mechanisms for this permeability are not well established. Endothelial permeability in other inflammatory states such as sepsis is driven primarily by overactivation of the RhoA GTPase. We hypothesized that tissue injury and shock drive endothelial permeability after trauma by increased RhoA acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Importantly, we also here provide evidence for the first time that 3K3A-aPC, which retains its cytoprotective function but has only approximately 5% of its anticoagulant function, abrogated the endotheliopathy/permeability after trauma. Furthermore, it has been previously shown that trauma-induced endothelial dysfunction is driven by a decreased Rac1/RhoA activation and associated loss of junctional integrity 19 . Building upon this ex vivo mechanistic data, we show that pre-incubation with aPC prior to treatment with ex vivo trauma plasma dramatically increases the Rac1/RhoA activation ratio, which corroborates our ECIS results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Importantly, we also here provide evidence for the first time that 3K3A-aPC, which retains its cytoprotective function but has only approximately 5% of its anticoagulant function, abrogated the endotheliopathy/permeability after trauma. Furthermore, it has been previously shown that trauma-induced endothelial dysfunction is driven by a decreased Rac1/RhoA activation and associated loss of junctional integrity 19 . Building upon this ex vivo mechanistic data, we show that pre-incubation with aPC prior to treatment with ex vivo trauma plasma dramatically increases the Rac1/RhoA activation ratio, which corroborates our ECIS results.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been previously shown that trauma-induced endothelial dysfunction is driven by a decreased Rac1/RhoA activation and associated loss of junctional integrity. 19 Building upon this ex vivo mechanistic data, we show that pre-incubation with aPC prior to treatment with ex vivo trauma plasma dramatically increases the Rac1/RhoA activation ratio, which corroborates our ECIS results. This suggests that aPC's barrier protective effects, which are driven through PAR-1 signaling, involve the Rac1 and RhoA GTPase signaling pathways.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…58 Wu et al 59 demonstrated that this binding activates an intracellular PAK-1 signaling pathway, which disassembles stress fibers to reduce endothelial permeability and maintain barrier integrity. DeBot et al 60 demonstrated that RhoA GTPase is activated after trauma and reduces endothelial permeability. RhoA GTPAse is upstream of PAK-1and likely is involved in the same pathway of endothelial protection.…”
Section: Potential Therapeutics To Mitigate the Eot Blood Productsmentioning
confidence: 99%